E-COMMERSE PROJECT DESIGN IN PT. LATOKA MINARYA - Apriyanti Nurhati Lawita; Drs. Lingga Hermanto, MM (Jurnal Sistem Informasi, 2004)
In writing this paper discusses the design of e-commerce project that would apply to companies engaged in maritime, where the sales made by companies other than sold to Indonesia also imported abroad. So it required a project design e_commerce to enable customers to obtain information. The writer tries to design an e-Commerce project into a concept view website. First the authors analyze the current system flowchart documents in the company, then the author tries to create a system that can facilitate the company in handling the product offering, namely through the internet along with an initial capital of thinking as an estimate, and project schedule. It is expected that after this project made the company can make it easier to exchange information to subscribers.